2013
DOI: 10.1088/0264-9381/30/13/135003
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology with scalar–Euler form coupling

Abstract: A coupling between the spacetime geometry and a scalar field involving the Euler four-form can have important consequences in General Relativity. The coupling is a four-dimensional version of the Jackiw-Teitelboim action, in which a scalar couples to the Euler two-form in two dimensions. In this case the first order formalism, in which the vierbein (or the metric) and the spin connection (or the affine connection) are varied independently, is not equivalent to the second order one, where the geometry is comple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…From the definition of torsion we see that this degree of freedom in both quantities is the same. This degree of freedom propagates to the curvature (a set of 2-forms dependent on 2 tetrad indices) in the form of the Weyl tensor components (24) and (25). It is absent in the metric, and also in the matter content, since the stressenergy τ a forms a set of 3-forms with a single tetrad index.…”
Section: Discussionmentioning
confidence: 99%
“…From the definition of torsion we see that this degree of freedom in both quantities is the same. This degree of freedom propagates to the curvature (a set of 2-forms dependent on 2 tetrad indices) in the form of the Weyl tensor components (24) and (25). It is absent in the metric, and also in the matter content, since the stressenergy τ a forms a set of 3-forms with a single tetrad index.…”
Section: Discussionmentioning
confidence: 99%
“…When V = const., this last term becomes a topological invariant proportional to the Euler characteristic and does not contribute to the field dynamics in the bulk, although it becomes relevant in the regularization of Noether charges for asymptotically locally anti-de Sitter spacetimes [82,83]. In the general case, namely V = const., this term contributes to the field equations acting as a source of torsion [51,[58][59][60][61][62][63][64]66]. The particular nonminimal coupling with the GB term we use is but one choice; the results regarding the speed of GWs are still valid even if the 1/ (Λ + κ 4 V ) coupling is replaced by an arbitrary function of (the magnitude of) the scalar field, f (|φ|).…”
Section: Scalar-tensor Model With Gauss-bonnet Couplingmentioning
confidence: 99%
“…When scalar fields are coupled to the Nieh-Yan topological invariant [52], a regularization procedure of the axial anomaly in RC spacetimes can be prescribed [53][54][55][56][57], and a torsion-descendent axion that might solve the strong CP problem in a gravitational fashion is predicted [58][59][60]. The nonminimal coupling to the Gauss-Bonnet invariant, on the other hand, can be motivated from dimensional reduction of stringgenerated gravity models [61], and it could drive the latetime acceleration of the Universe in the absence of the cosmological constant [62][63][64]. The first-order formulation of Chern-Simons modified gravity produces interesting phenomenology when coupled with fermions [65], and it has been shown that the different nonminimal couplings support four-dimensional black string configurations in vacuum, possessing locally AdS 3 × R geometries with nontrivial torsion [66].…”
Section: Introductionmentioning
confidence: 99%
“…[38]). More recently, this term has been show to lead to non-trivial torsional dynamics, and even more, it seems to have interesting consequences in cosmology [39,40].…”
Section: Discussionmentioning
confidence: 99%